Expression and clinical significance of S100A8/9 in adults with secondary phagocytic lymphohistiocytosis - Fang, Ziwei; Gao, Xin; Duan, Limin; Wang, Jujuan; Tian, Tian; Xu, Ji; Shu, Yongqian; Yin, Guangli; Qiu, Hongxia (Frontiers in Molecular Biosciences, 2025)
IntroductionThe study aimed to investigate the diagnostic and prognostic value of serum S100A8/9 levels with sHLHa, a high-mortality multiorgan inflammatory syndrome with no reliable clinical biomarkers, where calreticulin’s role is unclear.MethodsThis was a study of 67 newly diagnosed sHLHa patients. 48 patients met criteria and were analyzed. ELISA detected S100A8/9 levels in patients and controls. The optimal classification threshold for S100A8/9 was determined to be 2.44 µg/mL by restricted cubic spline (RCS) curve analysis. Patients were categorized. Correlations, diagnostic efficacy, survival differences, and prognosis impacts were analyzed.ResultsSerum S100A8/9 levels in sHLHa patients were greater than in healthy controls. Various analyses showed its diagnostic and prognostic value. ANC<1.0 × 109/L and high S100A8/9 expression group were independent risk factors for poor prognosis in patients with sHLHa. It’s correlated with liver function indicators and HScore.DiscussionThis study evaluates S100A8/9 in sHLHa diagnosis and prognosis. S100A8/9 levels are useful for differentiating patients, providing etiologic and survival info. They show a nonlinear positive correlation with survival and a threshold effect. Serum S100A8/9 levels offer potential biomarkers, and further studies are needed.